KEDUDUKAN HUKUM PURCHASE ORDER DALAM PERJANJIAN JUAL BELI MATERIAL ANTARA PT. PEMBANGUNAN PERUMAHAN (Persero), Tbk. dan TRIPUTRA KARYA UTAMA - Sinaga, Paulus Welly Andalanta; Yunari, Sri Bakti (Fakultas Hukum Universitas Trisakti, 2024)
In general, companies conduct buying and selling transactions using a purchase order as proof of ordering or purchasing. This purchase order document contains terms and conditions governing the sale and purchase conducted, without any preceding agreement. The legal position of a purchase order in a material sale and purchase agreement refers to contract law in accordance with Article 1320 of the Indonesian Civil Code (KUH Perdata). In the following case, involving PT. Pembangunan Perumahan (Persero), Tbk. and PT. Triputra Karya Utama, the payment for the sale and purchase was not made in accordance with the terms stated in the purchase order, and there was no underlying agreement preceding it. The issue at hand is how the legal standing of a purchase order in an agreement can be considered a valid contract under contract law, according to the provisions of the Indonesian Civil Code. Additionally, what legal remedies can PT. Triputra Karya Utama and PT. Pembangunan Perumahan (Persero) take in the event of a breach of contract? The type of research used is normative legal research, which is descriptive in nature. This study utilizes secondary data, primarily legal sources, obtained through literature studies and interviews. Data processing is carried out qualitatively, and conclusions are drawn deductively. Based on juridical analysis, the legal standing of a purchase order as an agreement fulfills the validity requirements of a contract under contract law and can be considered a valid agreement according to Article 1320 of the Indonesian Civil Code. Therefore, the material purchase order created by the parties, PT. Pembangunan Perumahan (Persero), Tbk. and PT. Triputra Karya Utama, constitutes a legally binding agreement that imposes rights and obligations on both parties. In the event of a breach of contract concerning the purchase order, the aggrieved party may demand performance of the contract or seek cancellation along with compensation, in accordance with Article 1267 of the Indonesian Civil Code.